Student’s Empowerment in Mathematics Classroom: Perception, Strategies, and States - Dhakal, Bed Prasad (Curriculum Development Journal, 2022)
Whatever the existing teaching-learning practices of mathematics education in our classroom, it is a time to escalate its effectiveness through sincere exploration of students’ empowerment. Empowering our students in mathematics classroom is a psychological, strategic and contingent to both mathematics’ teachers and students. This article argues that exploration of understanding of students’ empowerment, empowering strategies, and state of empowered mind are not fully studied yet. To capture the belief, understanding, perception, and practices of students’ empowerment in mathematics teaching and learning is the core concern of this paper. The secondary level mathematics teachers from the community schools of Kathmandu valley and mathematics educators were purposively selected. Descriptive exploration was made to discuss the information on three key focuses; perception of students’ empowerment, strategies for empowerment, and states of empowered students within the classroom premises. Opportunity of collaborative and cooperative engagement which accept the individual voice of students in the mathematics classroom is perceived as the strategies of students’ empowerment. Sufficient cognitive as well as affective actions that help to build the students’ strength in learning mathematics are the fundamental empowering strategies and the condition of happiness, satisfaction, and on task behaviour are the states of empowered students. Policy maker, academicians, and even the managers would take benefit from finding of this article. There are still many spaces to reduce the gap of existing and expecting strategies for students’ empowerment in the mathematics classroom.